Therapy and beyond : counselling psychology contributions to therapeutic and social issues - Milton, Martin; Wiley InterScience (Online service) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2010)
Therapy and Beyond: Counselling Psychology Contributions to Therapeutic and Social Issues presents an overview of the origins, current practices, and potential future of the discipline of counselling psychology. : Presents an up-to-date review of the knowledge base behind the discipline of counselling psychology that addresses the notion of human wellbeing and critiques the concept of'psychopathology' Includes an assessment of the contributions that counselling psychology makes to understanding people as individuals, in their working lives, and in wider social domains; Offers an overview of c.
Philosophical pluralism : navigating the sea of diversity in psychotherapeutic and counselling psychology practice / Donal McAteer -- Existential-phenomenological contributions to counselling psychology's relational framework / Elena Manafi -- Counselling psychology and research : revisiting the relationship in light of our'mission' / Deborah Rafalin -- Understanding human distress : moving beyond the concept of'psychopathology' / Martin Milton, Mark Craven, and Adrian Coyle -- Being with humans : an evolutionary framework for the therapeutic relationship / Frances Gillies -- Ethics : the fundamental dimension of counselling psychology / Camilla Olsen -- Different theoretical differences and contextual influences / Riccardo Draghi-Lorenz -- Humanistic contributions to pluralistic practice / Heidi Ashley -- Psychodynamic contributions to pluralistic practice / Debora Diamond -- Cognitive-behavioural contributions to pluralistic practice : reflection on an issue of some contention / Terry Boucher -- Amor fati : existential contributions to pluralistic practice / Elena Manafi -- The counselling psychologist working in a pain context / Natalie Hession -- Working with sport and exercise psychologists : a winning combination? / Jill Owen -- The'R' word / Joanna Lofthouse -- Counselling psychology contributions to understanding sexuality / Colin Hicks -- Counselling psychology contributions to religion and spirituality / Adrian Coyle -- Counselling psychology and the media : the highs and lows / Lucy Atcheson -- Coming home to roost : counselling psychology and the natural world / Martin Milton.
Includes bibliographical references and index.
Print version record.
Keywords: Counseling psychology; Counseling -- trends; Psychology, Clinical -- methods; Medicine; PSYCHOLOGY -- Psychotherapy -- Counseling; Counseling psychology; Electronic books